Teacher and peer feedback in collaborative learning: Perceived psychological ownership, perceived quality, and perceived learning outcomes - Chan, Michelle Mei Gwen; Nagaratnam, Shalini; Chew, Shin Yi; Mohamad Hanefar, Shamsiah Banu; Abd Naaz, Farah (Journal of Interdisciplinary Studies in Education, 2026)
While collaborative learning can enhance outcomes, it may reduce learners’ sense of ownership due to shared contributions and feedback. This study investigated the influence of teacher and peer feedback on perceived psychological ownership and learning in collaborative projects, assessing the mediating role of perceived quality and its impact on academic grades. Using a quantitative method with 132 Malaysian college students on a shared cloud platform, results showed that both peer and teacher feedback negatively influenced psychological ownership. Perceived quality partially mediated the relationship between psychological ownership and perceived learning. Furthermore, psychological ownership correlated positively with cognitive learning, but not emotional learning. These findings provide empirical evidence for improving collaborative learning environments by highlighting the importance of feedback sources and perceived quality.